Experiences of Intersubjectivity and Agency in Human-Horse Relationships Differ Between Box- and Open-Shed-Stable Environments - Koski, Sonja Elena (Taylor & Francis, 2025)
Human-horse relationships can be experienced in many ways and the horse companion can be given various roles, from a partner in action to a tool or commodity. How humans experience connection with horses and what kinds of roles are assigned to them may reflect or even depend on the real-life co-actions and environments. In this study, we assessed experiences of intersubjectivity in human–horse relationships, focusing particularly on whether and how agency and emotional and embodied intersubjectivity with the horse were discussed by horse owners. We conducted the study in two different stable environments, namely box stables and open-shed stables, that differ particularly in the horses’ possibilities to execute independent decision-making in their daily lives. We conducted semi-structured interviews of 25 horse owners and analyzed them using theory-guided qualitative content analysis for notions of agency and intersubjectivity. Overall, while there were only a few explicit accounts of embodied intersubjectivity in action, it was most explicitly apparent in descriptions of hacking and doing other things than riding. Additionally, intersubjectivity was apparent in descriptions of horse emotions. There were several differences in the horse owners’ accounts at the different stable environments. Respondents at the open-shed stables assigned agency more often to the horse or simultaneously themselves and the horse, discussed more often horse emotions, and emphasized hacking, playing, or just being with the horse as meaningful co-actions. At the box stables, accounts emphasizing competing, self-evidence of riding as the main activity, and human agency in co-action were more common. These results show that the management environment and forms of co-action are connected to the thoughts and views equestrians have on agency and experiences of intersubjectivity in horse–human relationships.